KONSEP NEW PUBLIC MANAGEMENT DALAM REFORMASI BIROKRASI PEMERINTAH PROVINSI BALI (Jurnal Nawala Politika, 2023)
One of the factors that influence good and bad governance lies in the bureaucracy. whether the bureaucracy is good or bad depends on the quality of the human resources of its apparatus, namely the state civil apparatus. the concept of New Public Management has begun to be implemented in Indonesia, one of which is Bali. This study uses a descriptive qualitative research technique by collecting various existing data. The implementation of the New Public Management is in the form of bureaucratic reform of the Bali provincial government with various new programs that are more modern, effective and efficient. The Provincial Government of Bali is of the opinion that the increase in the level of success in implementing bureaucratic reform in 2021 illustrates the success of the Provincial Government of Bali in implementing New Public Management in the form of Bureaucratic Reform. Keywords : New public management, bureaucratic reform, Pemprov Bali